HUBUNGAN PERILAKU BULLYING DENGAN TINGKAT KECEMASAN PADA REMAJA KELAS VIII DI SEKOLAH MENENGAH PERTAMA NEGERI 4 JOMBANG - Zahranie R.S, Qatrunnada Fitri; Rozi, Fahrur; Sholikhah, Dwi Uswatun; Sasmito, Nanang Bagus (LPPM STIKES HUSADA JOMBANG, 2024)
Background : The state of trauma in victim who experience bullying behavior will make mental health suffer and can lead to depression. Bullying behavior isn’t only by physically hite the victim, but can be verbal such as mocking, insulting, and spreading hoax which include bully behavior. The purpose of this study was to determine the relationship between bullying behavior and anxiety level in class VIII adolescents at junior high school 4 jombang. Objective : This research design use correlation analytic with a cross sectional approach. In this study, a population of 256 adolescents of SMPN 4 Jombang was obtained with a sample size of 80 respondents and using simple random sampling technique. Data collection tools in the form of questionnaire sheets and data analysis use the spearman rank test. Methods : The results of research conducted on adolescents at SMPN 4 Jombang show that almost all of the respondents experienced bullying behavior with a low category of 68 respondents (85.0%), while almost half of the respondents did not experience anxiety, 36 respondents (45.0%). Results : Based on the results of the spearman rank test, the significant value is obtained, namely < α (α = 0,05), is 0,000 < 0,05 meaning is accepted, it can be concluded that there is a significant relationship between bullying behavior and anxiety level. Conculison : Bullying behavior that occurs in adolescents of SMPN 4 Jombang is expected to understand the adverse effects of bullying and can sort out between good behavior and bad behavior to prevent bullying among schools and neighborhoods. The role of parents in the development of their children is very important so that children do not lack affection and thus prevent bullying cases from increasing.